Testing of a continuous monitoring system for water services and hygiene- Safely managed drinking water and sanitation systems in rural Kazakhstan - Ljungkvist,Viktor (TVVR 18/5011, 2019)
The drinking water and sanitation systems (WSS) in rural Kazakhstan have since its independence in 1991 been challenged with deteriorating implemented centralized systems where the population has been forced to explore individual, decentralized options to ensure a drinking water supply. With a limited documentation and classification of current WSS operating in rural settlements, the large-scale water programmes in recent years have been unsuccessful to improve conditions. By developing and testing a continuous monitoring system, where classification of operated systems follow international criteria, progression to more efficiently identify existing WSS and possible sustainability concerns is aimed to be achieved. By introducing classifications on decentralized systems, based on a safety level presented through the UN sustainable development goals, directly inquired by households through questionnaires administered by the local community, communication between households and institutions could be improved. The continuous monitoring system was tested in three villages during a field study to North-Eastern Kazakhstan, where 634 households (79% of total households) were successfully interviewed as well as local stakeholders and authorities. The villages visited were Chernoyarka, Novo-Chernoyarka and Sychyovka located north from the regional capital Pavlodar. By introducing an analysis tool to assess sustainability components to households or settlements with inadequate WSS, it could further specify the limitations contributing to challenges in the community. The sustainability components tested in this thesis are environmental, socio-cultural, institutional, economic, health and technological where each component is analysed through in-depth questionnaires enquired by 50 households in the visited villages. The results from the questionnaires showed limitations in technological implementations, where each household’s capacity and economic prerequisites determined installed WSS. Even though the majority of implemented systems meet basic levels of safety, the unregulated installation methods pose risks to operations. With limited institutional involvement, the prevailing systems are neither documented nor monitored to ensure a safely managed service or drinking water quality. By altering the approach towards rural WSS to improve already implemented decentralized systems, cost effective measures to more continuously monitor conditions and sustainability concerns could increase the trust between individual households and involved institutions. By financing drinking water analysis stations to be introduced and managed by local persons, capacity building and awareness of villagers would likely improve. Involving the community in the development and management process in rural settlements could be an initial step towards better communication with institutional improvement as well as increasing local capacity as a potential outcome.
Keywords: Kazakhstan; Drinking water; Sanitation; Hygiene; Communication; Monitoring system; Sustainable development; Classification